Ritual Pemakaman Turunan Bokeo di Kelurahan Silea Kecamatan Wundulako Kabupaten Kolaka - Runni Yanti Mansur; Laxmi Laxmi (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to determine the funeral ritual procession of Bokeo derivatives in Silea Village, Wundulako District, Kolaka Regency. This research uses Levi-Strauss (1958) Structural Theory Attitude of Relationship Between Relatives Elementally. The data collection technique used in this research is Snowball Sampling by conducting involved observation (observation participation) and in-depth interviews. this research is Qualitative research using Ethnographic research methods. The research shows that: first: when a bokeo descendant dies, several funeral ritual processes will be carried out, namely first; making a coffin from the trunk of an areca tree (pu'umbundi), second; wearing forty sarongs as a calendar (O'sawu), third; slaughtering buffaloes (To'ono Mogere) and fourth; funeral custom umbrella (O'pawu).